From Knowing to Remembering: The Semantic–Episodic Distinction - Renoult, Louis; Irish, Muireann; Moscovitch, Morris; Rugg, Michael D. (Trends in cognitive sciences, 2019)
The distinction between episodic and semantic memory was first proposed in 1972 by Endel Tulving and is still of central importance in cognitive neuroscience. However, data obtained over the past 30 years or so support the idea that the frontiers between perception and knowledge and between episodic and semantic memory are not as clear cut as previously thought, prompting a rethink of the episodic–semantic distinction. Here, we review recent research on episodic and semantic memory, highlighting similarities between the two systems. Taken together, current behavioral, neuropsychological, and neuroimaging data are compatible with the idea that episodic and semantic memory are inextricably intertwined, yet retain a measure of distinctiveness, despite the fact that their neural correlates demonstrate considerable overlap. Strong parallels exist between the theoretical frameworks underpinning retrieval of episodic and semantic information, including the proposal that both involve reinstatement or reactivation of neural representations of online experience.Activity of some, or possibly all, regions belonging to the ‘core recollection’ network may support the reinstatement of semantic processes engaged during an experience, rather than processes linked to episodic retrieval more generally.Mental time travel (the ability to re-experience the past and to ‘pre-experience’ the future) relies upon both episodic and semantic contributionsStudies of clinical populations converge to reveal considerable interdependencies between episodic and semantic representations during past- and future-oriented forms of memory.